Atomically thin photoanode of InSe/graphene heterostructure - Haihong Zheng; Yizhen Lu; Kai-Hang Ye; Jinyuan Hu; Shuai Liu; Jiawei Yan; Yu Ye; Yuxi Guo; Zhan Lin; Jun Cheng; Yang Cao (Nature Communications, 2021)
Achieving efficient photoelectrochemical cells requires insights into the ion kinetics at the surface of photoelectrode. Here, the authors show a new platform for investigating strong coupling between hydroxide ions and surface charge carriers by using monolayer InSe as the anode with high photocurrent density.